Получение кремния электродным восстановлением продуктов пиролиза рисовой лузги - Maronchuk, I. E.; Masenko, B. P.; Povstyanoy, M. V.; Zavadsky, V. A.; Solovyev, O. V. (PE "Politekhperiodika", Book and Journal Publishers, 2003)
A comparative analysis of the chemical properties of rice husk grown in Ukraine and several other countries has been carried out. A scheme for obtaining “solar‑grade” silicon from rice husk for the production of photovoltaic converters (PVC) is proposed. The process includes the following stages: washing of husk, pyrolytic decomposition of organic compounds, leaching, pyrolysis to obtain silicon dioxide, fabrication of electrodes of SiO₂–C (or metal) composition, electric arc reduction of silicon, and purification by crystallization.